2019
DOI: 10.31207/rch.v9i2.167
|View full text |Cite
|
Sign up to set email alerts
|

Uso del big data y de la automatización entre los profesionales de las relaciones públicas en Brasil

Abstract: El big data y la automatización se han convertido en dos grandes desafíos para la gestión estratégica de la comunicación en las organizaciones. El proceso de recogida, almacenaje y análisis de grandes cantidades de datos es clave a la hora de segmentar a los stakeholders, analizar el entorno, evaluar la eficacia de los procesos comunicativos y, en definitiva, responder de forma eficaz a las necesidades de los públicos. Sin embargo, y a pesar de las ventajas que conlleva el uso de esta tecnología, los profesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…Overall results do not show significant differences between the perception, diagnosis and forecast on the future evolution of communication management between a peripheral territorial analysis and similar researches carried out at national level (Dircom, 2015; Falkheimer et al, 2017; Marta-Lazo, 2014) or at supranational level, in the Latin American region (Moreno et al, 2015; Moreno et al, 2017; Moreno et al, 2019). The rise of online communication, social networks and the management of relations with users/audiences/public through mobile terminals has set the trend towards the globalization or standardization of strategic communication planning and implementation, which would be more oriented to select the most appropriate contact method in each geographic area rather than to defining the communication strategy itself (Etter et al, 2019).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Overall results do not show significant differences between the perception, diagnosis and forecast on the future evolution of communication management between a peripheral territorial analysis and similar researches carried out at national level (Dircom, 2015; Falkheimer et al, 2017; Marta-Lazo, 2014) or at supranational level, in the Latin American region (Moreno et al, 2015; Moreno et al, 2017; Moreno et al, 2019). The rise of online communication, social networks and the management of relations with users/audiences/public through mobile terminals has set the trend towards the globalization or standardization of strategic communication planning and implementation, which would be more oriented to select the most appropriate contact method in each geographic area rather than to defining the communication strategy itself (Etter et al, 2019).…”
Section: Discussionmentioning
confidence: 44%
“…Also, in the Latin American Communication Monitor (Moreno et al, 2015), online communication, social networks or mobile communication were activities expected to grow significantly. In addition, in the Latin American context, relations with traditional media are perceived as an activity in decline in the short term (Moreno et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to scholars' observations, between 2010 and 2019 women were still underrepresented in leadership positions (Place and Varderman Winter, 2018; Aleman et al , 2018; CIPR, 2018a; Tench et al , 2017; Soria and Gomez, 2017; Yeomans, 2014; CIPR, 2014b; Fitch and Third, 2014) and some data showed that number to be up to 80% (Dubrowski et al , 2019). In addition, studies showed that pay gap is a persistent problem and that both pay gap and the glass ceiling issues are still linked to the fact that women primarily occupy technical roles (Moreno et al , 2018a; Moreno et al , 2017; Moreno et al , 2015; CIPR, 2018a; Tench et al , 2017; Vardeman-Winter and Place, 2017; CIPR, 2017; CIPR, 2017a; CIPR, 2016b; CIPR, 2014a; Andrade and Sobreira, 2013; Pulido Polo, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Como se determinó en el estudio una de sus ventajas es automatizar las acciones de comunicación para, a través de algoritmos, identificar los contenidos de interés para determinado público, abaratando y acelerando el proceso de difusión de mensajes entre las organizaciones y sus públicos (Moreno et al, 2019).…”
Section: Discussionunclassified